(untitled) (The Research of Medical Science Review, 2025)
BACKGROUND: Subclinical hypothyroidism (SCH) is known to contribute to the progression of atherosclerosis and is closely linked to dyslipidemia a major risk factor for cardiovascular diseases, which significantly impacts morbidity and mortality rates. OBJECTIVE: To assess the dyslipidemia among patients diagnosed with subclinical hypothyroidism at Ghulam Mohammad Mahar Medical College Civil Hospital, Sukkur. PATIENTS AND METHODS: This descriptive, cross-sectional study was carried out over a six-month period (from 1st Sept-2024 to 28th Feb-2025) in the Department of Medicine at GMMMC, Civil Hospital Sukkur. Individuals aged 20 to 60 years, of either gender, diagnosed with subclinical hypothyroidism were included in the study. Participants were assessed for the presence of dyslipidemia. Both qualitative and quantitative variables were analyzed using frequency (percentages) and mean ± standard deviation (SD), respectively. RESULTS: A total of 144 individuals with subclinical hypothyroidism participated in the study. Among them, dyslipidemia was identified in 90 patients (62.5%). Most of those affected were female (56.2%), lived in urban areas (52.1%), and had a mid-level education (25.0%). Other notable characteristics among patients with dyslipidemia included smoking (43.8%), hypertension (61.1%), obesity (63.9%), non-alcoholic fatty liver disease (NAFLD) (56.9%), and diabetes mellitus (43.8%). CONCLUSION: Dyslipidemia is highly prevalent among individuals with subclinical hypothyroidism. Early detection and management are essential to reduce the risk of cardiovascular complications.